Anomalous boundary behavior of non-Newtonian fluids on amphiphobic surfaces. (January 2022) - Wang, Xingwei; Bao, Luyao; Wen, Jun; Dini, Daniele; Zhang, Jianbin; Sun, Li; Yang, Wufang; Zhou, Feng; Liu, Weimin
Abstract: In this work, the effect of amphiphobic surfaces on the rheological behavior and boundary slip of the shear thickening fluids (STFs) was investigated. The experimental results suggested the viscosities were diminished, shear thickening was delayed and weakened, and an ultrahigh drag reduction was obtained. Furthermore, slip length was observed to vary with shear rate. Dissipative particle dynamics (DPD) simulations were adopted to further investigate these specific rheology and slip behavior. The simulation results conformed with experiments and established a linear relationship between the slip length and viscosity. We consider this study could be a conducive practical reference for the investigation of boundary slip in complex fluids and possibly a crucial protocol for analyzing STFs' manipulation. Graphical Abstract: ga1 Highlights: The rheology for shear thickening fluid is changed, including diminished viscosity, delayed but weakened shear thickening. An ultrahigh drag reduction effect is achieved due to changed rheological behavior. An unconventional slip phenomenon is observed that is the slip length and viscosity form a linear relationship.